Information resources for action researchers/practitioners in Climate Resilient Agriculture - Gonsalves, Julian Francis; Dominguez, Dulce; Soria, Giulia; Vidallo, Rene R.; Bayot, Ruvicyn S.; Barbon, Wilson John; Soksophors, Yim; Bernardo, Eisen Bernard; Amutan, Celso (2020)
Most of the resources featured here were generated from actual climate-smart agriculture/climate resilient agriculture (CSA/CRA) programs implemented. Some of them reflect the action research nature of the CSA/CRA work of the International Institute of Rural Reconstruction in Asia, specifically in the Philippines, Cambodia, and Myanmar. This compilation includes publications generated from projects supported by the CGIAR Research Program on Climate Change, Agriculture and Food Security, Asian Development Bank, the International Development Research Station, the Latter Day Saints Charities, the Department of Agriculture in the Philippines and the Forest Foundation of the Philippines, among others. Some of these resources represent five years of field-derived experiences, now made available in their current form for those at the frontlines as part of efforts to address climate risks that affect smallholder farmers and family farms. Other references were drawn from desk researches.